2016
DOI: 10.1186/s40064-016-2625-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of methylated egg white proteins against pathogenic G+ and G− bacteria matching antibiotics

Abstract: Native egg white protein with high level of acidic amino acid residues (pI = 4.8) and hydrophilic nature was transformed into its methylated derivative (MEW), acquiring rather hydrophobic and basic character (pI = 8). The MIC of MEW against ten studied bacteria (G+ and G−) ranged between 0.5 and 1 μg/disc matching or excelling the comparative values of some known specific antibiotics (ranging from 1 to 7.5 μg/disc). Combinations of MEW (1 MIC) and different ready-made disc concentrations of antibiotics indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 25 publications
8
46
0
Order By: Relevance
“…Since S. aureus strain is a pathogenic bacterium, it was of interest to concentrate in this investigation on this pathogen rather than total staphylococci bacteria. The examined food samples showed themselves to be polluted with S. aureus bacterium (18% of tested foods), and this was interesting and showed that there is a need to continue to research annually to make updates about the microbial pollution of foods in Egypt to give certain attention to be careful with foods [ 9 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since S. aureus strain is a pathogenic bacterium, it was of interest to concentrate in this investigation on this pathogen rather than total staphylococci bacteria. The examined food samples showed themselves to be polluted with S. aureus bacterium (18% of tested foods), and this was interesting and showed that there is a need to continue to research annually to make updates about the microbial pollution of foods in Egypt to give certain attention to be careful with foods [ 9 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was aseptically collected in 100 mL screw capped bottles, transported to the laboratory. HB dilutions were prepared immediately prior their testing by diluting native honey to the required concentrations (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% v / v ) [ 10 , 21 ]. These dilutions were made using sterile distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats weighting 125 ± 10 g were housed in wire cages at room temperature (25 ± 5 • C) (five animals/cage). Animals were given food and water regularly and experienced 12 h light/dark cycles throughout the experimental period by oral route according to previous study in this respect [30,[71][72][73]. Afteracclimatization, ratsweredividedintofourgroups (five rats for each).…”
Section: Toxcicity Of Crude Oxbs and Histological Examinationmentioning
confidence: 99%
“…Natural agents have recently shown a promising potential to be used as therapy for either treatment of cancer or inhibition of multidrug pathogenic bacteria [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. They also possess an attractive property in that they are safe agents.…”
Section: Introductionmentioning
confidence: 99%